Potential Human Health Risks from Heavy Metals in Crayfish Shells Used as Food and Organic Fertilizer - Topal, Murat; Arslan Topal, E. Işıl; Öbek, Erdal (Springer Science and Business Media Deutschland GmbH, 2024)
Potential health risks of using waste crayfish shells as food and organic fertilizer were evaluated to protect health and environment. The heavy metals investigated can remain unchanged in receiving environments for a long time and can have negative effects on health. Hazard index (HI) values for man and woman were >1 for Cr, Co, V, La, and Mn in crayfish shells. HI values for child were greater than 1 for Ni, Cr, Mn, Co, V, La, and Pb in crayfish shells. There was a non-carcinogenic human health risk because of Ni, Cr, Mn, Co, V, La, and Pb for child. Total maximum carcinogenic value was 8.84E?03 for Ni whereas minimum value was 1.32E?05 for Pb. The potential carcinogenic risks in terms of dietary (Ni, Cr, and Cd) were higher than permissible values (1?×?10–4 to 1?×?10–6). A non-carcinogenic and carcinogenic potential health risk was determined in case of dietary intake of crayfish shells. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.
Keywords: Cancer; Contaminant; Crawfish; Health risk; Shell